Theoretical Foundations and Communicative Structure of the Media Text (Eurasian Journal of Philology Science and Education, 2025)
This article examines the theoretical foundations and communicative structure of media text within the context of language education. Media text is considered an interdisciplinary object of study that has emerged within contemporary media culture; its conceptual aspects and theoretical foundations are analyzed, and its key characteristics are identified. The study aims to systematize the concept of media text based on current scientific approaches and to determine the methodological possibilities of its application in language education. The research methods employed include theoretical analysis, comparative analysis, descriptive method, and methodological modeling. On this basis, the study identifies the socio-cultural features of media text perception and interpretation, as well as the conditions under which it is used in language education. Media text is regarded not only as a tool for information transmission but also as a complex socio-communicative phenomenon.The analysis systematizes five major approaches to media text research: critical, cognitive, cultural, participatory, and pedagogical. These approaches are shown to correspond with the use of linguistic, stylistic, narrative, semiotic, contextual, and discursive methods of analysis. Furthermore, the study applies Solganik’s concept of media text dynamics, which distinguishes three levels: intratextual, subtextual, and hypertextual.To address this multidimensionality, the study proposes a comprehensive model for analyzing media texts, integrating three dimensions: structural (genre and linguistic organization), pragmatic (audience orientation and social-regulative functions), and cultural (representation of values and cultural codes). The proposed model may serve as a methodological basis for future empirical studies and for advancing media literacy in educational practice.Keywords: media text, pragmatic feature, structural quality, cultural value, approaches and methods of analysis, text interpretation.